Marker assisted backcross selection for genetic removal of lipoxygenase-2 from popular soybean (Glycine max) variety JS 97-52: Parental polymorphism survey and hybridity validation - RAWAL, REENA; KUMAR, VINEET; RANI, ANITA; GOKHALE, S M; HUSAIN, S M (The Indian Journal of Agricultural Sciences, 2014)
Lipoxygenase-2 is the prime contributor to the off- flavour associated with the soy products. With the aim to introgress null allele of lipoxygenase-2 into popular soybean variety JS 97-52 through marker assisted backcross selection (MABC), parental polymorphism was surveyed for JS 97- 52 (recipient parent) and PI 596540 (the donor of null allele of lipoxygenase-2). A total of 264 SSR markers dispersed across 20 linkage groups were screened. Of these, 130 SSR markers showed polymorphism. SSR markers Satt522 and Satt656 reported to be in the vicinity of Lox2 locus were found to be polymorphic for JS 97-52 and PI 596540 and were used for confirming true F1 and BC1F1 plants. The polymorphic SSR markers identified in the study would be utilized for retrieving the genetic background of JS 97-52 in the backcross generations.